Gas adsorption, magnetic, and fluorescent sensing properties of four coordination polymers based on 1, 3, 5-tris(4-carbonylphenyloxy)benzene and bis(imidazole) linkers. Issue 47 (12th November 2018) - Zhang, Jie; Gao, Ling-Ling; Zhai, Li-jun; Wang, Xiao-Qing; Fan, Li-Ming; Hu, Tuo-Ping
Abstract : Four 3D novel coordination polymers (CPs) have been synthesized under solvothermal conditions. Furthermore, gas sorption behaviors revealed that complex1 has excellent selective separation for CO2 /CH4 . Abstract : Four 3D novel coordination polymers (CPs), formulated as {[Co3 (TCPB)2 (bibp)2 (dioxane)2.5 (H2 O)2 ]·(DMF)} n (1 ), {[Cd6 (TCPB)4 (bibp)4 (dioxane)(H2 O)2 ]·(dioxane)3 ·DMF·(H2 O)0.5 } n (2 ), {[Co1.5 (TCPB)(bimb)0.5 (DMF)(dioxane)]} n (3 ), and {[Zn1.5 (TCPB)2 (bimb)(DMF)(dioxane)2 ]·dioxane} n (4 ) (H3 TCPB = 1, 3, 5-tris(4-carbonylphenyloxy)benzene, bibp = 4, 4′-bis(imidazol-1-yl)biphenyl, and bimb = 1, 4-bis(imidazol-1-ylmethyl)benzene), have been synthesized under solvothermal conditions and characterized by elemental analyses (EA), single-crystal X-ray diffraction analyses, X-ray powder diffraction analyses (PXRD), IR spectra, and thermogravimetric analyses (TGA). The structural analyses reveal that complex1 can be simplified as a new 2-nodal (3, 10)-{3·4 2 }2 {3 4 ·4 10 ·5 14 ·6 14 ·7 2 ·8}-3, 10T3 net, complex2 has a 3D 2-nodal (3, 8)-c network with the point symbols of {4 2 ·5}2 {4 4 ·5 9 ·6 8 ·7 3 ·8 3 ·9}, complex3 exhibits a novel 3D framework with the point symbol of {4 10 ·6 32 ·7·8 2 }{4 3 }2, and the structure of4 is a (3, 8)-connected {4 3 }2 {4 6 ·6 18 ·8 4 }-tfz-d net. Furthermore, gas sorption behaviors of complex1 for N2, H2, CH4, and CO2 have been comprehensively studied at varying temperatures: the results reveal that the adsorption capacity of1 to N2 is stronger than those of other gases. Meanwhile, IAST calculations reveal that1 exhibits excellent selective separation for CO2 /CH4 . Magnetic measurements indicate that both1 and3 have antiferromagnetic interactions within the trinuclear clusters. In addition, the fluorescent measurements showed that2 and4 exhibit highly selective and sensitive detection of Fe 3+ and Cr 3+ ions.